The effect of organizational commitments in auditor performance with dysfunctional audit behavior as mediation variables - Putra, Made Doni Permana; Widanaputra, Anak Agung Gede Putu; Ramantha, I Wayan; Gayatri, Gayatri (International research journal of management, IT and social sciences, 2020)
Auditor performance is an act or the implementation of audit tasks that have been completed by the auditor within a predetermined period of time. One of the factors that influence auditor performance is organizational commitment and dysfunctional audit behavior. This study aims to empirically prove the effect of organizational commitment on auditor performance mediated by dysfunctional audit behavior. The population in this study were all auditors in KAP in all provinces of Bali. The sample was selected using the purposive sampling method with the criteria of auditors working on KAP for a minimum of one year. Data was collected through a survey method using a questionnaire. Hypotheses are tested by path analysis. Based on the results of the analysis it was found that organizational commitment has a positive effect on auditor performance and audit dysfunctional behavior is not able to significantly mediate organizational commitment to auditor performance. This is because an auditor who already has a commitment will do the best in carrying out his duties which causes his performance will increase, so that audit dysfunctional behavior is no longer significant in mediating the relationship of organizational commitment to auditor performance.